Wody Zofii Nałkowskiej - Marzec, Lucyna (Wydawnictwo Naukowe UAM w Poznaniu, 2011)
The article treats the aquatic imagination of Zofia Nałkowska in her early and late works. The matter of water is in Nałkowska’s writing strongly connected with an image of women, but, as the author claims, not in the way Gaston Bachelard pointed out in his works. Nałkowska throughout her writing attemped to re-think and re-write the Ophelia complex (or the Ophelia myth), indicating cultural and social aspects of women’s choices. The more adequate theory describing women’s relation with water is the one proposed in Luce Irigaray’s essays.
Waters of Zofia Nałkowska